ANALISIS WACANA KRITIS NOVEL NEGERI DI UJUNG TANDUK: PENDEKATAN MODEL FAIRCLOUGH (Critical Discourse Analysis of Negeri di Ujung Tanduk Novel: Fairclough Model Approach) - Syah, Saprudin Padlil; Ansoriyah, Siti; Rohman, Saifur (Kantor Bahasa Provinsi Sulawesi Tenggara, 2024)
A novel is a type of literary work created as an author's response to the context of his environment. This study aims to describe the textual level, the level of discourse practice, and the level of sociocultural practice in the Negeri di Ujung Tanduk Novel. This study used a descriptive qualitative approach. The source of data in this study is the novel Negeri di Ujung Tanduk by Tere Liye. The data obtained were analyzed using Fairclough's model of critical discourse analysis theory. Based on research, the following three things are known. First, the theme raised in this novel depicts power, ideology, and social norms in discourse. Second, based on the level of discourse practice, it is known that there is an interpretation of the text and context to the discourse. Third, based on the level of sociocultural practice, it is known that there is an external context that accompanies the discourse of the novel which includes three things, namely the situation dimension, the institutional dimension, and the social dimension. Novel merupakan jenis karya sastra yang dibuat sebagai respons pengarang atas konteks lingkungannya. Penelitian ini bertujuan untuk mendeskripsikan level tekstual, level praktik kewacanaan, dan level praktik sosiokultural pada novel Negeri di Ujung Tanduk. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Sumber data dalam penelitian ini adalah novel Negeri di Ujung Tanduk karya Tere Liye. Data yang diperoleh dianalisis menggunakan teori analisis wacana kritis model Fairclough. Berdasarkan penelitian diketahui tiga hal berikut. Pertama, yaitu tema yang diangkat dalam novel ini gambaran kekuasaan, ideologi, dan norma sosial dalam wacana. Kedua, berdasarkan level praktik kewacanaan diketahui adanya interpretasi teks dan konteks terhadap wacana. Ketiga, berdasarkan level praktik sosiokultural diketahui adanya konteks luar yang mengiringi wacana novel tersebut yang meliputi tiga hal, yaitu dimensi situasi, dimensi institusi, dan dimensi sosial.